Prevalence, associated factors, and perceived causes of mental distress among visitors to holy water in Mekelle town, Tigray, North Ethiopia - Berhe, Kenfe Tesfay; Mossie, Tilahun Belete; Teklemichael, Desalegn Massa (Frontiers in Psychiatry, 2025)
BackgroundIn low-income countries, mental disorders contribute to 12% of the global burden of disease compared to 8.1% in developed countries. Seeking help from religious institutions, which offer prayer and treatment with holy water, has been reported as a common strategy, particularly in developing settings. Despite the presence of many holy water sites in the study area, the problem has not been well studied. Therefore, this study aimed to assess the prevalence, associated factors, and perceived causes of mental distress among visitors to holy water sites in Mekelle town, North Ethiopia.MethodsA cross-sectional study design was employed, involving 380 participants in the quantitative study and 9 participants in the qualitative study, selected from three holy water sites in Mekelle town. Mental distress was measured using the Self-Reporting Questionnaire (SRQ-20). Data were analyzed with the Statistical Package for the Social Sciences (SPSS), version 20, and logistic regression analysis was used to determine associations at a p-value <0.05.ResultsAmong the 380 holy water visitors assessed, 147 (38.7%) had mental distress. Headache was the most commonly reported symptom, followed by feelings of fatigue and nervousness. The independent factors associated with mental distress were female sex (AOR = 1.68 (95% CI; 1.04, 2.72)), illiteracy (AOR = 3.2 (95% CI; 1.28, 6.91)), recent serious conflict with family members (AOR = 3.82 (95% CI; 1.89, 7.68)), and the belief that lack of faith causes mental illness (AOR = 2.33 (95% CI; 1.43, 3.79)).ConclusionThe prevalence of mental distress is high among holy water visitors compared to prior studies. This highlights the importance of engaging religious leaders and community members to integrate both religious and modern mental healthcare approaches.